Has Housing Policy for Low-Income Communities in Indonesia Undergone Significant Reform - Mendra Wijaya; Setyo Utomo; Abdul Aziz (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
This article critically examines Indonesia’s housing policies within the context of its intricate maritime geography, emphasizing persistent challenges despite constitutional commitments to housing rights. Indonesia, an archipelagic nation comprising over 17,000 islands, encounters unique logistical and infrastructural obstacles that complicate the implementation of effective housing strategies. The country faces a substantial housing deficit, with projections indicating a shortfall of approximately 12.75 million units by 2023, amid an annual demand estimated at between 800,000 and 900,000 units. Employing qualitative analysis, this study explores the multifaceted barriers impeding progress, including a predominant reliance on market-driven approaches and the limited efficacy of existing programs such as the Family Housing Savings Program (FLPP), the One Million Houses initiative, and Public-Private Partnership (KPBU) schemes. These measures have yet to significantly reduce the backlog, which is estimated to reach 15 million units by 2025. The research underscores that structural issues, such as inadequate funding, bureaucratic inefficiencies, and geographical dispersal, hinder policy effectiveness. To address these challenges, the study advocates for a more integrated, context-sensitive approach that combines government intervention with sustainable community-based solutions, ensuring equitable housing access across Indonesia’s diverse maritime landscape.